Detected The Sex Of Fish That Is Good For Cultivation Using Fuzzy - Satria Abadi; Fitriyani (Komunitas Dosen Indonesia, 2022)
Fish is a type of vertebrate animal that is poikilotermic (cold-blooded), has distinctive features on its spine, gills and fins and depends on water as a medium for life. Fish have the ability in the water to move by using fins to maintain the balance of their body so that it does not depend on the current or movement of water caused by the wind direction using the FMADM (fuzzy multi attribute decision making) method. The purpose of this study is to get the problem to be solved, namely making a decision support model using the FMADM (fuzzy multi attribute decision making) method with the help of image processing in determining the sex of fish to increase fish farming yields. The preferred alternative in the selection of fish sex is that the 4th alternative has the highest value as the best prospective fish brood with a weighting point of 0.57. Then the investigation is carried out using image processing which is processed using photoshop so that it can be calcified into three image creteria of the physical shape of the sex, and from the number of spines located on the fins of the fish.